The Periplus Maris Erythraei : Text with Introduction, Translation, and Commentary - Casson, Lionel, 1914-2009 (Book collections on Project MUSE., 1989)
The Periplus Maris Erythraei, "Circumnavigation of the Red Sea," is the single most important source of information for ancient Rome's maritime trade in these waters (i.e., the Red Sea, Gulf of Aden, and western Indian Ocean). Written in the first century A.D. by a Greek merchant or skipper, it is a short manual for the traders who sailed from the Red Sea ports of Roman Egypt to buy and sell in the various ports along the coast of eastern Africa, southern Arabia, and western India. This edition, in many ways the culmination of a lifetime of study devoted to Rome's merchant marine and her trade with the east, provides an improved text of the Periplus, along with a lucid and reliable translation, a comprehensive general commentary that treats in particular the numerous obscure place-names and technical terms that occur, and a technical commentary that deals with grammatical, lexicographical, and textual matters for readers competent in Greek. An extensive introduction places the Periplus in its historical context.